EFFECTS OF TEMPERATURE ON SURFACE DEFORMATION OF 2-D ENZYME MODEL USING LANGEVIN EQUATION - Azka Nasution, Habibi
Enzyme is vital components of human digestion especially in the process of eat and drink. The activity of enzyme in human mouth is exible and very sensitive to temperature, especially on the part of active site from the surface of the enzyme. we have to model the surface of the enzyme shaped bubble on the coordination of 2-D. The surface of the enzyme is composed of particles that behave like random motion. The random motion is raised with Langevin dynamics equation. Then from the random motion of the particles constituent of the surface of the enzyme we investigate the deformation that occurs due to the inuence of temperature and relation to the activity of the enzyme. Based on the simulation results, the temperature of 370C of the enzyme is in a state of optimum. While at a temperature of 500C and 600C the enzyme undergoes signicant surface deformation and is on the state of denaturation.